Ответ:3 - х²
Пошаговое объяснение:
x²-1)*(1/(x-1) - 1/(x+1) -1) =
= (x²-1)*( (х+1)/(x²-1) - (х-1)/(x²-1) -(х²-1)/(х²-1) ) =
= (x²-1)*( (х+1 - х+1 - х²+1)/(х²-1) ) =
= (x²-1)*( (3-х²)/(х²-1) ) = 3 - х²
Ответ:
-х^2+1
(х^2-1)(1:х-1-1:х+1-1)
(х^2-1)(-1+1-1)
(х^2-1)(-1)
-x^2+1
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:3 - х²
Пошаговое объяснение:
x²-1)*(1/(x-1) - 1/(x+1) -1) =
= (x²-1)*( (х+1)/(x²-1) - (х-1)/(x²-1) -(х²-1)/(х²-1) ) =
= (x²-1)*( (х+1 - х+1 - х²+1)/(х²-1) ) =
= (x²-1)*( (3-х²)/(х²-1) ) = 3 - х²
Ответ:
-х^2+1
Пошаговое объяснение:
(х^2-1)(1:х-1-1:х+1-1)
(х^2-1)(-1+1-1)
(х^2-1)(-1)
-x^2+1